Tuberculosis screening of travelers to higher-incidence countries: A cost-effectiveness analysis - Menzies Dick; Tan Michael; Schwartzman Kevin (BMC, 2008)
Abstract Background Travelers to countries with high tuberculosis incidence can acquire infection during travel. We sought to compare four screening interventions for travelers from low-incidence countries, who visit countries with varying tuberculosis incidence. Methods Decision analysis model: We considered hypothetical cohorts of 1,000 travelers, 21 years old, visiting Mexico, the Dominican Republic, or Haiti for three months. Travelers departed from and returned to the United States or Canada; they were born in the United States, Canada, or the destination countries. The time horizon was 20 years, with 3% annual discounting of future costs and outcomes. The analysis was conducted from the health care system perspective. Screening involved tuberculin skin testing (post-travel in three strategies, with baseline pre-travel tests in two), or chest radiography post-travel (one strategy). Returning travelers with tuberculin conversion (one strategy) or other evidence of latent tuberculosis (three strategies) were offered treatment. The main outcome was cost (in 2005 US dollars) per tuberculosis case prevented. Results For all travelers, a single post-trip tuberculin test was most cost-effective. The associated cost estimate per case prevented ranged from $21,406 for Haitian-born travelers to Haiti, to $161,196 for US-born travelers to Mexico. In all sensitivity analyses, the single post-trip tuberculin test remained most cost-effective. For US-born travelers to Haiti, this strategy was associated with cost savings for trips over 22 months. Screening was more cost-effective with increasing trip duration and infection risk, and less so with poorer treatment adherence. Conclusion A single post-trip tuberculin skin test was the most cost-effective strategy considered, for travelers from the United States or Canada. The analysis did not evaluate the use of interferon-gamma release assays, which would be most relevant for travelers who received BCG vaccination after infancy, as in many European countries. Screening decisions should reflect duration of travel, tuberculosis incidence, and commitment to treat latent infection.